2022
DOI: 10.1098/rstb.2021.0155
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects of nectar microbes on pollinator health

Abstract: Floral nectar is prone to colonization by nectar-adapted yeasts and bacteria via air-, rain-, and animal-mediated dispersal. Upon colonization, microbes can modify nectar chemical constituents that are plant-provisioned or impart their own through secretion of metabolic by-products or antibiotics into the nectar environment. Such modifications can have consequences for pollinator perception of nectar quality, as microbial metabolism can leave a distinct imprint on olfactory and gustatory cues that inform forag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 165 publications
0
17
0
Order By: Relevance
“…Microbes also use amino acids as a nitrogen source in nectar and change its pH [ 80 , 81 ]. In addition to reducing its nutritional value, microbial metabolism may add new compounds to nectar [ 82 ]. An extreme example is the high ethanol content in fermented yeast-containing nectar consumed by treeshrews in Malaysian rainforests [ 83 ].…”
Section: Sugarsmentioning
confidence: 99%
“…Microbes also use amino acids as a nitrogen source in nectar and change its pH [ 80 , 81 ]. In addition to reducing its nutritional value, microbial metabolism may add new compounds to nectar [ 82 ]. An extreme example is the high ethanol content in fermented yeast-containing nectar consumed by treeshrews in Malaysian rainforests [ 83 ].…”
Section: Sugarsmentioning
confidence: 99%
“…Water, usually ignored in the composition of nectar, is also a nutrient, and the water component of nectar is a major factor in its variability but also important for consumers. Phenotypic variation in nectar chemistry is common [ 50 ], and there is increasing evidence for effects of microbial contamination on nectar chemistry [ 51 ].…”
Section: Nutrients In Nectar and Pollen And Their Importance For Poll...mentioning
confidence: 99%
“…Martin et al . [ 51 ] looked beyond the endogenous gut microorganisms of pollinators, and review the potential effects of nectar microbes on pollinator health. Bacteria and yeasts in nectar alter its chemical composition, with negative (e.g.…”
Section: Microbial Influence On Pollinator Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Flowers harbor a diversity of microbes including archaea, bacteria, fungi, protists, and viruses (Table ). Collectively, the floral microbiome has potential to be an important mediator of plant reproduction. , As such, there is growing interest in taking an expanded, community-level perspective in studying the floral microbiome, not only for the potential to improve disease management but also our understanding of the extended floral phenotype, the role these communities play in pre- and postpollination processes, and the health of beneficial insects that rely on floral rewards. ,, In this perspective, we briefly review the current state of research on floral microbiome assembly and function in agroecosystems, as well as future avenues for research that could advance microbiome management and resulting outcomes for both disease control and insect-mediated ecosystem services. In particular, we strive to note both advances and gaps with respect to major research priorities identified for the management of plant-associated microbiomes in agroecosystems …”
Section: Introductionmentioning
confidence: 99%